HUBUNGAN DAKWAH SOSIAL DENGAN RESEPSI KELUARGA MUSLIM TERHADAP STDI IMAM SYAFI’I JEMBER PADA MASYARAKAT KRANJINGAN DAN TEGAL BESAR JEMBER - Yuhadi, Irfan; Fathan Jihadul Islam, Fathan Jihadul Islam; Deni Irawan, Deni Irawan (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2024)
Social da'wah is da'wah through social activities, or productive work involving social life. The reception of Muslim families towards STDI Imam Syafi'i Jember reflects how this Islamic educational institution is received by the community around the campus. The reception covered the attitudes, views and support of the community regarding the role and contribution of STDI Imam Syafi'i in society. The approach used in this research is a quantitative approach with a correlation research type to determine the relationship between social preaching and Muslim family reception towards STDI Imam Syafi'i Jember. The population of this research is the Kranjingan and Tegal Besar Jember communities. The total sample in this study was 227 people taken using simple random sampling technique. The results of the research show that there is a significant positive relationship between social da'wah and Muslim family reception towards STDI Imam Syafi'i Jember in the Kranjingan dan Tegal Besar Jember communities. So the higher the social preaching, the higher the reception of Muslim families towards STDI Imam Syafi'i Jember. The level of relationship between social da'wah and the reception of Muslim families towards STDI Imam Syafi'i Jember is a strong relationship. Keywords: social preaching; reception; muslim family.